Dark peril : a Carpathian novel - Feehan, Christine (Feehan, Christine. Dark series., 2011)
Dominic of the Dragonseeker Carpathians is on a desperate mission in the heart of enemy territory when he crosses paths with Solange Sangria, the last of the jaguar people, who is trying to save shape-shifting women from her murderous father.